Penerapan ISO/IEC 29119-3 dalam Analisis dan Pengujian Sistem Informasi Perpustakaan Berbasis CodeIgniter 3 (Studi Kasus: Perpus Goldsop) - Maemunah, Atik; Al-Bawazir, Syifa; Anwar, Chairul (Journal of Information Systems and Business Technology, 2025)
Software testing is a crucial stage in the development of information systems, as it serves to ensure system quality, reliability, and conformity with user requirements. Information systems that are implemented without standardized testing procedures are prone to functional defects, operational disruptions, and a decline in user trust. Therefore, Software testing must be conducted in a systematic, structured, and well-documented manner. This study aims to evaluate the quality of the Goldsop Library Information System by applying the international standard ISO/IEC 29119. This standard is used as a guideline for test documentation development, test execution, as well as the recording and analysis of findings identified during the testing process. The testing process is carried out by designing Test cases that represent the core system functionalities and executing them to assess the conformity between expected outcomes and actual system behavior. Any Failures identified during testing are recorded as Bugs and classified according to their level of Severity. The results of the testing indicate that not all system functions operate as expected. Several findings with major Severity levels were identified, particularly affecting core system functionalities related to data validation and information delivery to users. In addition, this study also includes accessibility and scalability testing to assess the system’s readiness for broader usage conditions. Based on the testing results, the system still requires improvements and refinements before it can be recommended for optimal implementation.